Economic Crime Prevention Strategy in the Trade Sector to Create Healthy and Fair Business Competition - M. Arif Syahputra; Zudan Arief Fakrulloh (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2025)
This study explores the critical role of law in preventing and addressing crimes within the trade sector, focusing on specific economic crimes such as corruption, embezzlement, market manipulation, and smuggling. These crimes are on the rise, primarily driven by social and economic inequality. Unequal wealth distribution, weak regulatory oversight, and legal loopholes create opportunities for individuals and groups to pursue illicit financial gains. Powerful economic entities often exploit these weaknesses to maintain monopolistic control, deepening inequality and obstructing fair competition. Moreover, inadequate law enforcement and a lack of transparency within bureaucratic systems contribute to the widespread practices of bribery and collusion between business actors and government officials. This undermines the effectiveness of existing regulations and diminishes public confidence in the legal framework. The consequences of such economic crimes extend beyond financial losses; they significantly affect the broader society. These include rising poverty and unemployment, the deterioration of public trust in legal institutions, and increased social instability, all of which threaten sustainable economic development. To address these challenges, this study applies criminological and legal perspectives, underlining the necessity of multisectoral collaboration. It advocates for stronger government and legal institutional efforts, along with active community engagement, to enhance oversight mechanisms and promote transparency. Firm and equitable enforcement of laws is essential in ensuring justice and restoring trust. Ultimately, a collective commitment to legal reform and accountability is vital to building a trade environment that is fair, inclusive, and conducive to long-term national growth.